Adalékok a területfejlesztéssel kapcsolatos fogalmak vitájához - Faragó, László (Tér és Társadalom, 1994)
The currently running law- and decree making process (and also the communication among researchers dealing with regional issues) is made more difficult by the fact that the concepts in connection with regional planning are not clear. For this reason in the first part of his work the author makes a suggestion for the interpretation and the system of these concepts. He interprets regional development as a category that comprehends, organises the conscious control of the spatial processes and divides it into four subcategories: the regional political, the management, the organisational/institutional one and the one that contains the means. In the second topic he deals with the interpretation of the concept of the region, because in his opinion this is the least clarified regional basic category and the their formation is on schedule in Hungary these days. This chapter, besides raising theoretical issues, contains suggestions of the EU, as well. Finally the author is searching the answer to the ideological determination of regional development. This latter attempt can be defined as an innovative one, since the election experiences of last year show that in the programmes of the majority of the parties the regional policy was the least established one. Also, the representatives of the field and science – probably due to their aversion from politics- have not published in this topic. Comparing the regional policies in accordance with the conservative, liberal and social democratic values and the actual governmental behaviours the author gets to the conclusion that regional development, both in governmental and local levels, is maínly affected by objective regional processes, not by the political character of the power. The ideological platform defines the style and the means of the regional policy rather than its content. In international comparison the national features are much stronger than the similarity deriving from the ideological identities of the parties in power.